Semiotic Analysis of Roland Barthes on the Lyrics of "HOPE" by XXXTENTACION - Rais, Fadhil Maulana; Fadillah, Dani (Jurnal Audiens, 2025)
This research aims to find out the meaning in the lyrics of the song "HOPE" by XXXTENTACION using Roland Barthes' theory. The research method used is qualitative by collecting data through Roland Barthes semiotic analysis. The song, released in 2018, tells the story of the Parkland incident in which 17 people died and 14 were injured during the Stoneman Douglas High School shooting in Parkland, Florida. X the songwriter struggled with his mental health and was always suicidal. However, he made a promise to his friends and fans that he would never commit suicide. Roland Barthes' semiotic analysis will dig deeper into the meaning of each verse in the lyrics of the song "HOPE" by XXXTENTACION using elements of denotation, connotation, and myth, and is expected to make writers and readers understand well the meaning contained in the song "HOPE". The results showed that the denotation meaning in the lyrics of the song "HOPE" is to commemorate the shooting of students in Parkland, Florida and the connotation meaning in the lyrics of the song "HOPE" is to encourage listeners who are depressed not to end their lives. While the mythical meaning of the song lyrics "HOPE" is a message from the song owner that every problem must have a way out.